Faktor Perilaku dan Kegiatan Tamu Hotel dalam Pemakaian Air Hotel di Yogyakarta - Kombang Hananto (Ideas Publishing, 2022)
Scarcity of groundwater can cause conflicts between hoteliers and the surrounding community, because hotels use a lot of ground water. Researchers are interested in reviewing the use of groundwater in hotels, the results can be used as a reference for managing water use. This research was conducted in Yogyakarta by taking samples at two hotels, namely GIM and NSY , four-star standard hotels with 222 rooms and 206 rooms. The data comes from 210 respondents for the GIM hotel and 202 respondents for the NSY hotel, besides that it comes from interviews and questionnaires for hotel managers and staff. The findings on water use are that the average volume of water use per person per day for the NSY hotel is more (316 liters) than the GIM hotel (280 liters). There is a very strong correlation between shower/bathhub use and the total volume of water use r = 0.893 for the GIM hotel and r = 0.980 for the NSY hotel. There is a negative correlation between frequency and duration of shower use, which means that the more often you use the shower, the shorter the duration. Water use by gender, women use 61% more water than male guests 39% for GIM hotels while 64% women and 36% men for NSY hotels. This finding can be used as a reference for managing groundwater use through regulations so as not to cause conflict with the surrounding community and as part of realizing an environmentally friendly green economy.